Pengembangan Media Pembelajaran Berbasis Powerpoint Interaktif Materi Pantun Kelas IV - Sulastri; Delviani, Ummi; Gusmita, Amelia (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2025)
This research aims to develop interactive Powerpoint-based learning media on pantun material for elementary school students. The research method uses the systematic (ADDIE, Analysis, Design, Development, Implementation, and Evaluation) model. The development process includes needs analysis, media design, product development, implementation, and evaluation. The resulting interactive media is equipped with interesting animations, audio and quizzes, so as to increase student engagement and understanding. Product trials show that this media is effective in increasing students' motivation and interest in learning. Respondents gave positive assessments to the material, language and media aspects, with an average percentage of 100% conformity. The research results show that interactive Powerpoint media can be an innovative solution for learning rhymes that is more interesting, effective and efficient.